The rebuilding of a city: the restoration of the Temple of Diana in Évora - Cátedra, María (Revista de Antropología Social, 2011)
This article reflect a key issue about the symbolic elaboration of a museum-city of Évora, actually a World Heritage City. After the restoration of the Temple of Diana in the XIX century, the people from Évora perceived visually and cognitivelly the Roman origin of their city. The monument, in the top of the city hill, reestructured the whole city and made up its latter image. An image which did identify the city, as its exlibris, and impress its history. After a turbulent process, the cultivated defenders of the temple would propiciate other further iniciatives and build up a pioner and pervasive effort for protection and defense of the city.
Keywords: Urban Anthropology; restoration; patrimony; image; Évora